A Review on Anti-Breast Cancer Activity of Selected Medicinal Plants - Samathoti, Dr. Prasanthi (Asian Journal of Pharmaceutics (AJP), 2024)
To review and identify medicinal plants and bioactive substances with potential anti-breast cancer activity and provide a complete overview for future research. A comprehensive analysis of all scientific studies, phytochemical screening, ethnobotanical surveys, plant medicinal applications, and anti-breast cancer activities of medicinal plants was conducted. These data were gathered by searching for relevant articles in databases such as PubMed, Scopus, Google Scholar, and Web of Science. Relevant studies included those published in peer-reviewed journals and reports from respective conservation agencies. The reviewed medicinal plants and their bioactive components demonstrated promising anti-breast cancer activities, including antiproliferative, apoptotic, anti-angiogenic, and antioxidant activities. This study emphasizes the potential of medicinal plants and their bioactive chemicals for the treatment of breast cancer. This is a significant resource for future research and the development of effective plantbased medicines. Herbal medications are promising alternatives to traditional chemotherapy, with fewer side effects and greater tolerability. Further research is required to fully understand the anti-breast cancer capabilities of these medicinal plants and their bioactive components.